The Role of Working Memory on Dual-Task Cost During Walking Performance in Childhood - Rabaglietti, Emanuela; De Lorenzo, Aurelia; Brustio, Paolo Riccardo (Frontiers in Psychology, 2019)
This study examined the effect of a secondary motor task on walking ability, whether performance differed according to age and the possible relationship between cognitive abilities, specifically working memory, and dual-task costs in children with typical development. Fifty-three female children (mean age M=10±2 year), were divided into two different age groups: a young (7-9 years; n=17) and an older group (10-13 years; n=36). First, participants performed a Walking Test (WT) without additional tasks; afterwards, they performed the same walking test while performing each of the following tasks: carrying (1) a glass of water, (2) a ball on a round tray and (3) the combination of both tasks (1) and (2). The Test of Memory and Learning were used to assess working memory. WTs under a dual-task condition generally produced worse results compared to a single-task condition [F(3,135)=32.480, p<0.001. No age-related difference was observed [F(1,45)=0.497, p=0.485] . Age, digit forward and backward, facial memory and paired recall accounted altogether for 28.6% of variance in dual-task ability during WT while carrying a glass of water and a ball on a round tray. Specifically, facial memory significantly accounted for the variance of DTC in WTWT (β=-0.381, p=0.016). Moreover, a trend toward a statistical significance was observed for digit forward (β=-0.275, p=0.085). Results underlined that regardless of the age, a dual-task performance might affect walking performance depending on the required secondary task. Moreover, our results showed the association between working memory skills and dual-task cost in walking ability.